Relationship between knowledge and awareness with ergonomics practices among police officers - Engkannah, Vishnu (2021)
This study aims to identify the level of knowledge and awareness of ergonomics among Police officers in the State of Selangor. Based on the table Krejcie and Morgan (1970) this study required a total of 175 samples as study respondents. The results of descriptive analysis showed that the level of knowledge and awareness were at a high level with mean values of 4.55 and 4.40, respectively. Next, Pearson Correlation analysis showed that there was a relationship between these two variables with a coefficient value of r of 0.796. The implication of this study is that the police officers in the State of Selangor can identify the importance of expanding knowledge and thus, creating awareness of ergonomics. Effective ergonomic practices can ensure the quality of personal health. Therefore, all parties, especially the police officers and heads of departments should organize measures to ensure that all officers in the workplace have the appropriate level of knowledge and awareness to ensure ergonomic practices in the workplace.